As estratégias de produção em The Ren & Stimpy Show: O reconhecimento pelo desenho animado da década de 1990 - Kuhne, Manoel Carlos Aguiar (2020)
This work aims to identify the production strategies present in the animated production of the 1990s, The Ren & Stimpy Show (1991), which resulted in an audience phenomenon for its time in a series of controversies regarding its content. Through the theoretical-methodological repertoire of Cultural Studies, a mapping of producers involved in the animated series is carried out, in order to reveal the encodings that allowed them to address the public. Through the theoretical intertwining with the object of study, it was possible to see several strategies by which production is done, recognition to its audience